Parameters Optimization of Dissimilar Friction Stir Welding for AA7079 and AA8050 through RSM - Kavitha, M.; Manickavasagam, V. M.; Sathish, T.; Gugulothu, Bhiksha; Sathish Kumar, A.; Karthikeyan, Sivakumar; Subbiah, Ram (Advances in materials science and engineering, 2021)
Aluminium alloy is widely used in engineering application, and it can be classified based on the constituent elements or alloying elements. Aluminium alloy is preferred for the nature of its tensile strength, ductility, and corrosion resistance in this research to make a dissimilar friction stir welding joint of aluminium alloys 7079 and 8050 materials. The tensile strength of the weld joint is estimated by the influence of the response surface methodology approach. The welding is carried out by preferred process parameters with a tool speed of 1000–2500 rpm, tool pin diameter of 2–6 mm, welding speed of 50–300 mm/min, and tool shoulder diameter of 10–20 mm. The ANOVA analysis and the prediction of tensile strength were conducted efficiently. From the RSM analysis, the tool pin diameter mostly modified the output of the result.